Análisis de la cartera de crédito vencida de Yamaha de la ciudad de Babahoyo del periodo 2017 y 2018 - Li Moyano, Liliana (2020)
The present study was carried out at the Yamaha warehouse in the city of Babahoyo in which the past due loan portfolio of the period 2017 and 2018 was analyzed. This type of commercial house applies strategies such as ease of payment that can be beneficial in attracting customers. and increase sales for the store, however, this advantage brings with it the risk that the store must assume if the client does not cancel definitively or is behind on his payments and therefore it is difficult to recover the credit portfolio. Carrying out an adequate analysis of the client's conditions to grant the credit is one of the primary ways to minimize risk, but such management is not only the factors that depend on having a healthy collection management, but also those of the client. The Yamaha store presented late payments in its credit portfolio, which caused an increase in the delinquency of the portfolio and therefore the turnover of the portfolio is not correct for the store, this annual collection being a low percentage, it is say a slow recovery of accounts receivable.